Microbiota characterization throughout the digestive tract of horses fed a high-fiber vs. a high-starch diet - Raspa, Federica; Chessa, Stefania; Bergero, Domenico; Sacchi, Paola; Ferrocino, Ilario; Cocolin, Luca; Corvaglia, Maria Rita; Moretti, Riccardo; Cavallini, Damiano; Valle, Emanuela (Frontiers in Veterinary Science, 2024)
Diet is one of the main factors influencing the intestinal microbiota in horses, yet a systematic characterisation of the microbiota along the length of the digestive tract in clinically healthy horses, homogenous for age and breed and receiving a specific diet is lacking. The study used 16S rRNA amplicon sequencing to characterise the microbiota of the intestinal tracts of 19 healthy Bardigiano horses of 14.3 ±0.7 months of age fed one of two diets. Nine horses received a high-starch diet (HS), and ten horses received a high-fibre diet (HF). After 129 days, the horses were slaughtered, and samples were collected from the different intestinal tract compartments. The microbiota alpha diversity indices were lower in the caecum, pelvic flexure and right dorsal colon of the horses fed the HS diet (False Discovery Rate, FDR<0.05). The values of beta diversity indicated significant compositional differences between the studied intestinal tract compartments according to the diet received (FDR<0.05). At the lower taxonomic level (genus or family), the HS diet was associated with a higher relative frequency of Enterobacteriaceae within the small intestine (jejunum and duodenum) (FDR<0.05). Within the hindgut (caecum and sternal flexure), the HS diet was associated with lower relative frequencies (i.e. a smaller core community) of bacteria belonging to Fibrobacteraceae and Prevotellaceae (FDR<0.05). Moreover, horses fed the HS diet displayed a higher relative abundance of Streptococcus in the caecum (FDR<0.05) and Fusobacterium in the sternal flexure (FDR<0.05), both of which are pathogenic bacteria responsible for inflammation diseases. Samples collected from the pelvic flexure and rectum of horses fed the HS diet showed significantly higher relative frequencies of Succinivibrionaceae (FDR<0.05)amylolytic bacteria associated with acidosis. The relative frequencies of the Lachnospiraceae and Ruminococcaceae were lower in the faeces collected from the rectum of horses receiving the HS diet vs HF diet, indicating smaller core communities of these bacteria (FDR<0.05). Fibrous diets should be promoted to prevent dysbiosis of the microbiota associated with high-starch diet.